Kaleidoscopic Odessa : history and place in contemporary Ukraine - Richardson, Tanya (University of Toronto Press, 2008)
"Ukraine's 'Orange Revolution' and its aftermath exposed some of the deep political, social, and cultural rifts running through the former Soviet republic. This book explores the intersection of these divisions in Odessa, a Black Sea port in Ukraine that was once the Russian Empire's southern window to Europe. Odessans view their city as a cosmopolitan place with close ties to Russia and the world despite the state's attempt to generate feelings of national belonging. Odessans' sense of place is cultivated in various urban spaces through the narration of histories that are both intimate and official, imperial and local, traumatic and nostalgic. In illuminating the interplay of history with competing senses of place and nation in Odessa, this study shows how nation-building policies interact with the legacies and memories of the Russian Empire and the Soviet Union."--Jacket.
Keywords: Odesa (Ukraine) -- History.; Odesa (Ukraine) -- Social conditions.; Ethnology -- Ukraine -- Odesa.; Sociology, Urban -- Ukraine -- Odesa.; Odesa (Ukraine) -- Biography.; Odessa (Ukraine) -- Histoire.; Odessa (Ukraine) -- Conditions sociales.; Odessa (Ukraine) -- Biographies.; Ethnologie -- Ukraine -- Odessa.; Sociologie urbaine -- Ukraine -- Odessa.; 15.70 history of Europe.; HISTORY -- Europe -- Eastern.; HISTORY -- Europe -- Former Soviet Republics.; HISTORY -- Europe -- Russia & the Former Soviet Union.; SOCIAL SCIENCE -- Anthropology -- General.; Social conditions; Sociology, Urban; Ukraine -- Odesa; Kollektives Gedächtnis; Odessa; Odesa.; Geschichte; Ethnology -- Ukraine -- Odesa; Odesa (Ukraine) -- History; Odesa (Ukraine) -- Social conditions; Biographies; History